Agriculture Finance Diagnostic : Zambia - World Bank (World Bank, Washington, DC, 2020)
The agricultural sector plays a critical role in the Zambian economy. The share of the agriculture sector's GDP financed by the banking sector is among the highest in Africa. Nearly half the population is working in agriculture. Yet less than 5 percent of institutional credit goes to small and medium scale farms. Recent gains in financial inclusion of farmers, driven by the rapid growth in access to mobile money, present a key foundation on which to build. The Zambia Agriculture Finance Diagnostic identifies several key actions the Government can take to realize these opportunities. The high priority actions include providing incentives to the private sector to deliver financial services in rural areas, strengthening the capacity of the recently-established Zambia Credit Guarantee Scheme to effectively serve the agriculture sector, and strengthening the design and implementation of the weather index insurance scheme. The report also recommends that the Government consider developing an agriculture finance action plan that is adequately resourced and allocates clear implementation responsibilities.